Umur bibit 25 hari dan bibit kultur jaringan jenis Kappaphycus alvarezii terhadap pertumbuhan dan kandungan karaginan - Djami, Dewiyanti; Ratoe Oedjoe, Marcelien Dj; Rebhung, Felix (Jurnal Aquatik, 2024)
This research was conducted to determine the growth rate and carrageenan content in Kappahycus alvarezii seaweed by comparing the use of 25-day-old selection seeds, unselected seeds and tissue culture seeds. This research was carried out in Oenaek waters for 3 months. observations of growth directly in the cultivation site while for carrageenan content were carried out at the Undana FPKP Laboratory. The results showed that the use of 25-day-old selection seeds can increase the growth rate and carrageenan content in seaweed. The highest absolute growth reached 267.8 grams, while the highest daily growth was 5.146%/gr as well as the carrageenan content which reached 6.32%. Keywords: Selected seeds aged 25 days, carrageenan content, Kappaphycus alvarezii.